2022
DOI: 10.1177/20420986221116468
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge, and attitude toward adverse drug reaction (ADR) reporting among healthcare professionals in Ghana

Abstract: Background: Spontaneous reporting systems are the commonest means of reporting adverse drug reactions (ADRs) worldwide. Under-reporting remains a challenge particularly in developing countries among healthcare professionals (HCPs) who are considered the primary stakeholders in the reporting of ADRs. The challenge with studies in countries such as Ghana is that the focus has been on a single professional group or health facility. This study examines the rate of reporting as well as awareness, knowledge, and att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…The outcomes of the research show significant rates of underreporting (0.006029% for antiglaucoma and 0.003552% for artificial tear); this indicates a worrying result since the pillar of pharmacovigilance focuses on spontaneous reporting [18]; also, underreporting limits obtaining sufficient data to generate risk minimization activities, representing a significant threat to the population [19]; for this reason, there is a need to encourage reports in pharmacovigilance, especially in ophthalmic due there is evidence that the notification in ophthalmology is less than other medical specialties [20,21]. Additionally, underreporting seems to be selective for some factors like seriousness, severity, gender and unexpected ADRs.…”
Section: Discussionmentioning
confidence: 96%
“…The outcomes of the research show significant rates of underreporting (0.006029% for antiglaucoma and 0.003552% for artificial tear); this indicates a worrying result since the pillar of pharmacovigilance focuses on spontaneous reporting [18]; also, underreporting limits obtaining sufficient data to generate risk minimization activities, representing a significant threat to the population [19]; for this reason, there is a need to encourage reports in pharmacovigilance, especially in ophthalmic due there is evidence that the notification in ophthalmology is less than other medical specialties [20,21]. Additionally, underreporting seems to be selective for some factors like seriousness, severity, gender and unexpected ADRs.…”
Section: Discussionmentioning
confidence: 96%
“…These findings were consistent with a previous study conducted in Thailand [ 38 ]. A higher value was reported in Saudi Arabia (71.3%) [ 51 ], Oman (69.2%) [ 52 ], Pakistan (67.6%) [ 17 ] and Ghana (66.7%) [ 53 ]. However, lower proportion of ADR reporting among pharmacist as compared to our findings was observed in Kuwait (26.8%) [ 54 ], Jordan (19.5%) [ 55 ] and Syria (10.8%) [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, more than half (60.4%) of the HCPs were untrained about PV and ADR reporting. Previous studies conducted in Nigeria (86.5%) [ 27 ], Saudi Arabia (76.3%) [ 80 ], South Africa (68.3%) [ 81 ], Ethiopia (55.5%) [ 15 ], Finland (48%) [ 48 ], and Ghana (37.1%) [ 53 ] reported that various proportion of HCPs had no training on PV and ADR reporting. Our results also showed that lack of training was the predictors of poor ADR reporting practice among HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the research show significant rates of underreporting (0.006029% for antiglaucoma and 0.003552% for artificial tears); this indicates a worrying result since the pillar of pharmacovigilance focuses on spontaneous reporting [ 18 ]; additionally, underreporting limits the obtainment of sufficient data to generate risk minimization activities, representing a significant threat to the population [ 19 ]; for this reason, there is a need to encourage reports in pharmacovigilance, especially in ophthalmics due to is evidence that the notifications in ophthalmology are reduced compared to other medical specialties [ 20 , 21 ]. Additionally, underreporting seems to be selective for some factors, such as seriousness, severity, gender, and unexpected ADRs.…”
Section: Discussionmentioning
confidence: 99%